The Conceptual Framework of Aircraft Nationality within the Scope of Private International Law A research paper extracted from the master`s thesis entitled The provisions governing aircraft nationality in private international law - Ramadan, Rozhin Samir Ramadan; Hassan, Prof.Dr. Mohammed Jalal Hassan (Sulaimani Journal for Humanities, 2025)
Civil aviation is considered a vital public utility, especially with the increasing interconnection between states, the growth of tourism among individuals, the expansion of foreign trade, and the advancement of technological methods in various aspects of public life as a means of use across different fields. As a result, the aircraft has become an essential manifestation of modern civilization, a fundamental pillar of contemporary society, and a steady indicator of the progress of nations.The nationality of an aircraft holds significant legal importance, as it enables the determination of the nationality of births occurring on board during its flight within national or foreign airspace, or over free airspace (the high seas), as well as during its landing at a national airport. The research addresses the core issue by identifying the connecting factor or criterion according to which nationality is granted to the aircraft. National laws and relevant international conventions—such as the Paris and Chicago Conventions on Civil Aviation—have adopted regulations governing aircraft nationality and the legal effects arising therefrom as a result of legal acts and factual events occurring on board during flight or at airports.The study examines the concept of aircraft nationality through specific definitions, classifications, legal nature, and the foundations for granting nationality according to defined criteria that establish its affiliation with a particular state. As movable property, the aircraft may constitute an object of rights and generate legal effects vis-à-vis third parties.Accordingly, the rules governing aircraft nationality constitute an important connecting factor for determining the applicable law to legal acts and factual events, as well as for establishing judicial jurisdiction within the framework of private international law. Within this conceptual framework, the research clarifies the concept of the aircraft and its nationality through doctrinal, terminological, and legal definitions, as well as through international conventions and comparative legislation, highlighting the various scholarly perspectives on its definition and its role in determining legal jurisdiction over relationships occurring on board aircraft.The study also presents juristic trends ranging between denial and recognition of granting nationality to aircraft, based on the provisions of international conventions and domestic legislation. It adopts the legal principle that each state has the authority to determine the conditions for granting its nationality to aircraft under its own legislation, including registration requirements within its territory, which vary from one state to another. States also grant aircraft the right to fly their flag, as these conditions are considered guarantees for consolidating state sovereignty over the aircraft, in accordance with their economic circumstances, which differ based on material and technical capabilities and are influenced by adopted economic policies.Most national legislations rely on aircraft registration as the primary criterion for granting nationality, including comparative legal systems in general. Iraqi legislation also adopts the registration criterion, while additionally requiring the nationality of the owner as a condition for registration. Consequently, the state retains the freedom to determine the conditions under which nationality is granted to aircraft. Granting nationality to aircraft serves to protect, to a certain extent, the interests of states in the field of air navigation. It represents one of the most prominent foundations of private international law and a key legal pillar as an original connecting factor, through which the aircraft’s affiliation with a specific state can be determined, and on the basis of which disputes arising from legal acts and factual events occurring on board may be resolved.
Keywords: Aircraft; Nationality; Legal Nature; International Conventions; Comparative Laws